Occlusal bite force changes during 6 months of orthodontic treatment with fixed appliances - Alomari Sawsan A.; Abu Alhaija Elham S. (Sciendo, 2012)
Background: Occlusal bite force (OBF) is reported to change during fixed appliance orthodontic treatment.